INDONESIA’S ROLE IN THE INDIAN OCEAN REGION COOPERATION: POST-IORA CHAIRMANSHIP STRATEGIES - Briliantina Putri (Jurnal PPI Dunia, 2018)
The Global Maritime Fulcrum (GMF) vision announced by President Joko Widodo in 2014 marked a neworientation on how Indonesia see its maritime strategic environment. Indonesia has for many years focused onthe Asia Pacific because the region is more conducive for trade liberalization and economic integration. TheGMF requires Indonesia to look beyond Asia Pacific and give more attention to the Indian Ocean region.Indonesia has been an active member of the Indian Ocean Rim Association (IORA), a regional forum that seekto enhance economic cooperation in the Indian Ocean region. This paper explains the importance of IORAcooperation for Indonesia, its relevance to the GMF vision, and Indonesia’s contribution to the IORA duringits Chairmanship from 2015 to 2017. It argues that during the Chairmanship, Indonesia has given more weightto IORA’s geopolitical significance in two ways: normative-ideational and institutional initiatives. This paperalso recommends three post-chairmanship strategies that Indonesia can continue to pursue: norms building,institutional building and capacity building. These initiatives are important to provide stronger platform forIORA’s development. A successful IORA cooperation will eventually support Indonesia to realize the GMFgoals, particularly in its effort to strengthen Indonesia’s position and presence in the Indian Ocean region.